Pengamanan Aplikasi Menggunakan Algoritma Camelia - Emerson Porman Malau (Jurnal Informatika Kaputama (JIK), 2019)
Safeguarding Applications Using the Camelia Algorithm is a software that can assist in securing or locking an application file, where the file can no longer be opened by anyone except the owner of the file. In this research the locking and reopening process of the application file is performed using the Camelia Algorithm , So that it produces a software that can lock and open an application file.